Epizootology and Molecular Diagnosis of Lumpy Skin Disease among Livestock in Azerbaijan - Zeynalova, Shalala; Asadov, Kliment; Guliyev, Fizuli; Vatani, Mahira; Aliyev, Vidadi (Frontiers in Microbiology, 2016)
Lumpy skin disease (LSD) is a viral disease of livestock that can cause cutaneous and internal lesions, affecting milk production, hide quality and in some cases death of the infected animal. After an outbreak in neighboring Iran, a working group from the Azerbaijan State Veterinary Control Service was sent to the border rayons (administrative districts) to determine if any cattle in southern Azerbaijan were infected. The Rayonal Veterinary Offices were contacted to look for and report any cases of LSD in their rayons. Animals exhibiting clinical signs consistent with LSD infection were first observed in the rayon of Bilasuvar and more cases were subsequently identified in Jalilabad, Ujar, and Aghdash rayons. Samples were collected from blood, and/or lesions of suspected infected animals and internal organs of cattle that died and were tested at the Republican Veterinary Laboratory in Baku using real-time polymerase chain reaction (PCR). From June to November 2014, 2,762 cattle in Azerbaijan were reported to have clinical signs or gross necropsy lesions consistent with LSD. Of 269 samples tested for LSD virus by real-time PCR, 199 (74%) were positive. A total of 33 cattle died, which was 1.2% of those exhibiting clinical signs of disease. Samples from nodular cutaneous lesions were more frequently positive by PCR and had higher concentrations of virus than blood and pooled internal organ samples. Preventative measures including movement restrictions, vector control and vaccination were put into place to slow the spread of disease. Ongoing surveillance should continue as environmental persistence of the virus may lead to further outbreaks of disease.